Know my name : a memoir - Miller, Chanel ([New York, New York] : Viking, an imprint of Penguin Random House LLC, 2019)
Brock Turner had been sentenced to just six months in county jail after he was found sexually assaulting "Emily Doe" on Stanford's campus. Her victim impact statement was posted on BuzzFeed, where it instantly went viral, was translated globally, and read on the floor of Congress. It inspired changes in California law and the recall of the judge in the case. Now Miller reclaims her identity to tell her story of trauma, transcendence, and the power of words. She tells of her struggles with isolation and shame during the aftermath and the trial, reveals the oppression victims face in even the best-case scenarios, and illuminates a culture biased to protect perpetrators. --
Keywords: Miller, Chanel; Rape victims -- United States -- Biography; Women -- Crimes against -- California -- Stanford -- Case studies; Rape -- California -- Stanford -- Case studies; Rape in universities and colleges -- California -- Stanford -- Case studies; Sentences (Criminal procedure) -- California -- Case studies; Judicial error -- California -- Case studies; Trials (Rape) -- California -- Case studies; Sex discrimination in justice administration -- California -- Case studies; Rape -- Universities and colleges; Victimes de viol -- Biographies; Femmes -- Crimes contre -- Californie -- Stanford; Californie -- Stanford; Californie; Erreur judiciaire -- Californie; Californie; Discrimination sexuelle dans l'administration de la justice -- Californie; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; BIOGRAPHY & AUTOBIOGRAPHY / Women; SOCIAL SCIENCE / Sexual Abuse & Harassment; Miller, Chanel; Rape victims -- United States -- Biography; Women -- Crimes against -- California -- Case studies; Rape -- California -- Case studies; Rape in universities and colleges -- California -- Case studies; Sentences (Criminal procedure) -- California -- Case studies; Judicial error -- California -- Case studies; Trials (Rape) -- California -- Case studies; Sex discrimination in justice administration -- California -- Case studies; True crime stories; Case studies; Autobiographies; California -- Stanford; United States; Trials (Rape); Sex discrimination in justice administration; Sentences (Criminal procedure); Rape; Judicial error; Rape in universities and colleges; Rape victims; Women -- Crimes against; California -- Stanford; California; United States; Miller, Chanel; Rape victims -- United States -- Biography; Women -- Crimes against -- California -- Stanford -- Case studies; Rape -- California -- Stanford -- Case studies; Rape in universities and colleges -- California -- Stanford -- Case studies; Sentences (Criminal procedure) -- California -- Case studies; Judicial error -- California -- Case studies; Trials (Rape) -- California -- Case studies; Sex discrimination in justice administration -- California -- Case studies; Victims of crimes -- Biography; Biography; Autobiography; True crime stories; Case studies; Autobiographies